Task-technology fit assessment of the proposed information system for the National Commission on Indigenous Peoples - Baluyut, Emmanuel M. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Philippines – a country filled with diverse culture, beliefs, and history. With the forthcoming of its invaders, there are still several indigenous groups who upheld the every culture of being a Filipino. The National Commission on Indigenous Peoples (NCIP) supports these groups as the representative of the government. One of the struggles of the agency was disaggregated data (Indigenous Peoples’ International Centre for Policy Research and Education), specifically the demographic information of the ICCs/IPs (R. Dingal, Personal Communication, 2019).